Phenotypic detection of carbapenem resistance and metallo-beta-lactamase among Enterobacteriaceae from clinical samples in tertiary care hospital - Agarwal, Nidhi; Chauhan, Sapna; Singh, Paramjit; Sharma, V. K. (International Journal of Research in Medical Sciences, 2019)
Background: Carbapenems have the broadest activity spectra of any β-lactam antibiotic and are often the most appropriate agents for use in the treatment of infections caused by multi resistant gram negative bacteria. The recent worldwide emergence and dissemination of carbapenemase-producing Gram negative rods that are resistant to carbapenems is a significant concern with respect to patient care and infection control strategies. Hence this study was undertaken to study the magnitude of carbapenem resistance among routine clinical isolates of family Enterobacteriaceae so as to guide the clinicians in selection of appropriate antimicrobial chemotherapies and infection control measures. Methods: The present study was conducted in the Department of Microbiology over a period 18 months from January 2017 to July 2018. All the clinical isolates of Enterobacteriaceae were screened for carbapenem resistance as per CLSI guidelines. Such strains were then subjected to phenotypic confirmation of carbapenemase production by the Modified Hodge test. All isolates that gave a positive screening test were further evaluated for metallo-β-lactamase production. The technique used was the Combined Disk Test using a combination of Imipenem and Imipenem-EDTA. Results: Out of the 400 total clinical isolates of Enterobacteriaceae isolated in the laboratory,57 were found to be Meropenem resistant (14.25%) and were labelled ’Carbapenem resistant Enterobacteriaceae" or CRE. Modified Hodge test (MHT) performed on the 57 carbapenem resistant isolates showed 41 (71.93%) isolates to be carbapenemase enzyme producers. Combined disc test (CDT) conducted on the 57 isolates of CRE detected Metallo-β-lactamase (MBL) enzyme production in 39 isolates (68.42%). Conclusions: Since there is a high prevalence of carbapenemase resistance in our setting hence we need to be cautious with the indiscriminate use of broad spectrum antimicrobials, more so, the carbapenems.